Career choices for ophthalmology made by newly qualified doctors in the United Kingdom, 1974-2005 - Lambert, T; Goldacre, M; Bron, A (BioMed Central, 2008)
Background: The paper aims to report trends in career choices for ophthalmology among UK medical graduates. Methods: Postal questionnaire surveys were undertaken of qualifiers from all UK medical schools in nine qualification years since 1974. Data were analysed by univariate cross-tabulation. The significance of comparisons between groups of doctors were calculated by the use of chi-squared tests and adjusted residuals. Results: Ophthalmology was the first choice of long term career for 2.3% of men and 1.5% of women one year after qualification; 2.0% of men and 1.4% of women three years after; and 1.8% of men and 1.2% of women at five years. Comparing early choices with eventual destinations, 64% who chose ophthalmology in year one, 84% in year three, and 92% in year five eventually practised in the specialty. The concordance between year one choice and eventual destination was higher for ophthalmology than for most other specialties. 'Enthusiasm for and commitment to the specialty' was the most important single factor in influencing career choice. The prospect of good working hours and conditions was also an important influence: it influenced career choice a great deal for a higher percentage of those who chose ophthalmology (66% in the third year) than those who made other surgical choices (23%). Conclusion: Those choosing ophthalmology show a high level of commitment to it. Their commitment is strengthened by the prospect of attractive hours and working conditions. Many doctors who become ophthalmologists have already made their choice by the end of their first post-qualification year.